Palliative care: general aspects, pain control and the role of the anesthesiologist (Research, Society and Development, 2023)
Palliative Care emerges as a humanitarian philosophy of caring for patients terminally ill, alleviating their pain and suffering. These precautions foresee the action of an interdisciplinary team, where each professional, recognizing the limits of his action will contribute to the patient, in a terminal state, having dignity in his death. Specifically in the field of anesthesia, the expansion of palliative care is even more recent, verifying that the challenges for the anesthetist who assists the patient what requires care palliatives he comes increasing due to the growing progress obtained with the new techniques of analgesia and sedation. Caring in anesthesia palliative care is intended to provide comfort, provide the other with their own care and give you O power in if blame per that. Among these news techniques stands out the controlled analgesia for the patient (ACP).